2018
DOI: 10.1021/acsnano.8b05283
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Induced Localized Nanoscale Polymer Reflow for Three-Dimensional Self-Assembly

Abstract: Thermal reflow of polymers is a well-established phenomenon that has been used in various microfabrication processes. However, present techniques have critical limitations in controlling the various attributes of polymer reflow, such as the position and extent of reflow, especially at the nanoscale. These challenges primarily result from the reflow heat source supplying heat energy to the entire substrate rather than a specific area. In this work, a focused ion beam (FIB) microscope is used to achieve controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…3D graphene nanoarchitectures (Figure ) can be realized by an origami-like self-assembly technique where the melting of a hinge is utilized to generate a surface tension force that folds 2D patterns into 3D structures. ,, Diverse 2D graphene patterns were used to achieve three distinct types of hollow 3D graphene architectures, namely, 5-faced square pyramids (Figure d–f), 5- or 6-faced cubes (Figure j–l,s-u), and cylindrical tubes (Figure p–r) with heat energy supplied from hot plates, focused ion beams, and exothermic reactive ion etching. Raman spectroscopy of the samples before and after self-assembly was used to assess changes in the properties of graphene before (Figure c,i,o) and after self-assembly (Figure f,l,r).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D graphene nanoarchitectures (Figure ) can be realized by an origami-like self-assembly technique where the melting of a hinge is utilized to generate a surface tension force that folds 2D patterns into 3D structures. ,, Diverse 2D graphene patterns were used to achieve three distinct types of hollow 3D graphene architectures, namely, 5-faced square pyramids (Figure d–f), 5- or 6-faced cubes (Figure j–l,s-u), and cylindrical tubes (Figure p–r) with heat energy supplied from hot plates, focused ion beams, and exothermic reactive ion etching. Raman spectroscopy of the samples before and after self-assembly was used to assess changes in the properties of graphene before (Figure c,i,o) and after self-assembly (Figure f,l,r).…”
Section: Resultsmentioning
confidence: 99%
“…Two methods are possible to leverage the large surface and volumetric enhancements in 3D cubes and pyramids. First, it has been shown that, even in 5-faced cubic graphene containers, single large area hotspot can be induced due to one of the faces (bottom surface) experiencing uniform orthogonal coupling from all directions . Second, the targeted molecules can also be encapsulated within these 3D geometries by using biocompatible energy sources for generation of highly localized self-assembly triggers such as heating prestressed hinges to 37 °C (optimum body temperature) or magnetic field-based assembly. , Furthermore, the volumetric field can excite atoms in the bulk volume, not only those near the surface of graphene, thus, achieving higher carrier generation to deliver fuel cells with lower reaction temperatures and photodetectors with a higher efficiency and low response time.…”
Section: Discussionmentioning
confidence: 99%
“…The approach is straightforward and scales favorably, suggesting potentially widespread applicability in micro‐ and nano‐manufacturing. This versatile technique is compatible with planar lithographic techniques such as photo‐, e‐beam, nanoimprint, and soft lithography, as well as with direct ink writing and 3D printing. Hence, for the first time now, it is conceivable that extremely complex particles could be assembled with precise shape and surface patterning in a highly reproducible manner.…”
Section: Resultsmentioning
confidence: 99%
“…Self‐folding cubes can be used as a scaffold to suspend novel atomistic materials such as graphene and graphene oxide to create novel electromagnetic devices . Joung et al demonstrated tunable optically transparent self‐folded polyhedra with freestanding graphene oxide panels and solder hinges (Figure e) .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation